Determinants of Return on Assets and Asset Growth In KBMI Group 4 Commercial Banks: Determinants of Return on Assets and Asset Growth In KBMI Group 4 Commercial Banks - pratiwi, Wigati; Sofilda, Eleonora; Suparyati, Agustina (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2025)
The banking industry plays a crucial role in a nation's economy, especially for Indonesia, as developing countries, hence the financial performance of the bank should be maintained continuously to support the real sector. Observing the determinant factors about their performance over time are challenging works, because it might be resulted in variative direction. Therefore, this study have a main objectives where to re-analyse the factors. This study using several variables divided into two terms internal (CAR, NPL, LDR, OER, and NIM) and external (GDP, Inflation rate, and BI Rate) that affect profitability rate and asset growth in Indonesian largest capitalized bank. Panel data regression and VECM are conducted by the author using capitalized commercial banks (KBMI 4) between 2017-2023. Several variables reveal consistent results in the long-run where CAR, LDR, Inflation rate, and BI Rate have positive influence on profitability rate. Furthermore, CAR (+), NPL (-), GDP (-), and BI Rate (+) also reveal a consistent impact toward asset growth. Several implications, especially for governments, of this result further discussed in the last sections.